(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Self-regulated learning (SRL) strategies are essential for academic success, particularly in challenging subjects like chemistry. Understanding how these strategies and students’ attitudes influence chemistry achievement can inform educational practices and policies. This study investigates the dynamics of self-regulated learning and attitudes of students in chemistry achievement in secondary A mixed-methods approach was employed, involving 400 senior secondary school students from various schools in South-South Nigeria. Participants completed a structured questionnaire that included the Self-Regulated Learning Strategies (SRLS) scale and the Chemistry Attitude Scale (CAS). Additionally, focus group discussions were conducted to gain deeper insights into students’ attitudes and learning strategies. Data were analyzed using descriptive statistics, Pearson correlation, and The findings revealed a significant positive correlation between self-regulated learning strategies and chemistry achievement (r = 0.52, p < 0.01). Students who frequently used SRL strategies, such as goal setting, self-monitoring, and self-evaluation, demonstrated higher achievement in chemistry. Attitudes towards chemistry also played a crucial role, with a positive attitude significantly enhancing the effectiveness of SRL strategies (r = 0.47, p < 0.01). The regression analysis indicated that SRL strategies and attitudes together accounted for 35% of the variance in chemistry achievement (R² = 0.35, p < 0.01). The study highlights the importance of fostering self-regulated learning strategies and positive attitudes towards chemistry to improve student achievement. Educational interventions should focus on training students in effective SRL techniques and promoting a positive learning environment. Policymakers and educators in South-South Nigeria should consider these factors to enhance chemistry education and overall academic performance.